Halal Marketing Transformation: The Influence of Digital Halal Label on Generation Z Consumers' Purchase Intentions - Mulia, Mohammad Rafazthody Hafiz; Setyaning, Alldila Nadhira Ayu (PT FORMOSA CENDEKIA GLOBAL, 2024)
Digital halal labeling plays a vital role in halal product marketing, particularly for Gen Z consumers. This study examines the influence of halal brand image on purchase intention through factors such as perceived quality, satisfaction, trust, and loyalty among 210 Indonesian Gen Z consumers. SEM-PLS analysis reveals that a strong halal brand image enhances these factors, which in turn increases purchase intention. However, the study is limited to Indonesian Gen Z consumers. It recommends that companies utilize digital marketing to strengthen brand trust and loyalty. Future research should broaden the demographic scope and employ longitudinal methods to track changes in consumer behavior over time.